2021
DOI: 10.3390/su13179773
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CSR and Ethical Leadership to Shape Employees’ Pro-Environmental Behavior in the Era of Industry 4.0. A Case of the Banking Sector

Abstract: The phenomenon of corporate social responsibility (CSR) is an ever-evolving concept due to its multidimensionality. However, a plethora of studies have investigated CSR to achieve different organizational-related objectives, and its potential link to shape employee’s extra-role behavior, especially employee pro-environmental behavior (EB) in the era of Industry 4.0, is underexplored in the literature. To bridge this gap, the current study aims to explain the relationship between CSR and EB with the mediating r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 131 publications
(153 reference statements)
0
17
0
Order By: Relevance
“…To this end, the study confirms the mediation role of an ethical leader to explain a positive association between CSR and employees’ pro-environmental behavior. Recently, some other scholars have also mentioned the mediating effect of leadership to explain the discretionary behavior of employees [ 142 , 143 ].…”
Section: Discussionmentioning
confidence: 99%
“…To this end, the study confirms the mediation role of an ethical leader to explain a positive association between CSR and employees’ pro-environmental behavior. Recently, some other scholars have also mentioned the mediating effect of leadership to explain the discretionary behavior of employees [ 142 , 143 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ethical leadership refers to a leadership style that is characterized by respect for ethical norms, values, and dignity for the work through interactive communication and involving them in organizational decision-making (Wu et al, 2021). Ethical leadership plays a role model in developing followers' commitment (Abuzaid, 2018;Sharma, et al, 2019) Ethical leadership is reported to influence normative commitment (Abuzaid, 2018;Danish et al, 2020;Lotfi et al,2017;and Sheraz, 2020)…”
Section: Public Service Motivation Mediates the Influence Of Ethical ...mentioning
confidence: 99%
“…Transformational leadership theory has been regarded as an important driver of employee behavior and company strategy [20][21][22][23][24][25]. Indeed, transformational leadership has been studied across different disciplines [26][27][28][29][30].…”
Section: El and Ecsrmentioning
confidence: 99%